1964
DOI: 10.1149/1.2426306
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Adsorption and Oxidation of Carbon Monoxide on Platinum Using Constant Current Pulses

Abstract: Using single anodic constant‐current pulses, the steady‐state concentration of carbon monoxide already adsorbed on the surface of a bright Pt electrode in 1MH2SO4 and the additional amount of CO adsorbed during the application of the pulse has been determined. At potentials of 0.3–0.4v (NHE), surface coverage of one molecule of CO per surface Pt atom was observed at very low CO partial pressures; for CO partial pressures up to 1 atm the coverage increased to about 1.06 CO molecules per Pt atom, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1966
1966
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…and independent of CO partial pressure from 0.0037 to 1 atm. 156 The value in the absence of CO, i.e., with helium, was 0.29 V (N.H.E.). In 1 N HCI0 4 at 30°C, the rest potential of CO on smooth Pt was reported to drift slowly from 0.4 to 0.1 V (N.H.E.…”
Section: (I) Overall Reactionmentioning
confidence: 97%
“…and independent of CO partial pressure from 0.0037 to 1 atm. 156 The value in the absence of CO, i.e., with helium, was 0.29 V (N.H.E.). In 1 N HCI0 4 at 30°C, the rest potential of CO on smooth Pt was reported to drift slowly from 0.4 to 0.1 V (N.H.E.…”
Section: (I) Overall Reactionmentioning
confidence: 97%
“…It is possible (4-6) that the first step in the oxidation of MeOH is the oxidation of the hydroxyl hydrogen as (CH3OH) ads --> (CH~O)ads -k H + + e [3] One may visualize further, with the discharge of three more electrons in acid solutions, the oxidation of the remaining three hydrogens of the methyl group giving successively (HeCO) ads, (HCO) ads, and finally (CO)ads. The over-all reaction would be (CH3OH) ads --> (CO)ads -t-4 H+ -t-4e [4] Warner and Schuldiner (17) have shown that CO is strongly adsorbed on Pt. To remove the CO involves the discharge of a molecule of H20, and probably, as suggested by Warner and Schuldiner, the CO reacts rapidly with the adsorbed oxygen atoms produced by the discharge of H20.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulties have been commented on since 1965 when Brummer and Ford [2] sought to clarify some discrepancies in the charges associated with oxidising complete CO ads adlayers in the work by Gilman [3], and Warner and Schuldiner [4], by correcting for oxide formation and double layer charging.…”
Section: Introductionmentioning
confidence: 99%